2015
DOI: 10.3892/mmr.2015.4540
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics-based optimization of neuroleukin-mediated regulation of articular chondrocyte proliferation

Abstract: Due to the low proliferative and migratory capacities of chondrocytes, cartilage repair remains a challenging clinical problem. Current therapeutic strategies for cartilage repair result in unsatisfactory outcomes. Autologous chondrocyte implantation (ACI) is a cell based therapy that relies on the in vitro expansion of healthy chondrocytes from the patient, during which proliferation-promoting factors are frequently used. Neuroleukin (NLK) is a multifunctional protein that possesses growth factor functions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Future research projects may offer mechanistic insights into the NLK regulation of chondrocytes growth. [ 358 ] In an endeavor to design an OC unit‐on‐a‐chip model including functional cartilage and bone tissue units, Goldman et al. [ 159 ] developed a microfluidic chip incorporating bovine MSCs‐derived OC constructs.…”
Section: Development Of Cartilage‐related Organ‐on‐chipsmentioning
confidence: 99%
“…Future research projects may offer mechanistic insights into the NLK regulation of chondrocytes growth. [ 358 ] In an endeavor to design an OC unit‐on‐a‐chip model including functional cartilage and bone tissue units, Goldman et al. [ 159 ] developed a microfluidic chip incorporating bovine MSCs‐derived OC constructs.…”
Section: Development Of Cartilage‐related Organ‐on‐chipsmentioning
confidence: 99%
“…As the most recent advancement in the palette of 3D culture techniques, organ-on-a-chip (OOAC) and microphysiological systems (MPS) aim for an even better recapitulation of a native tissue-like environment, tissue architecture and cell-specific responses relevant to OA modeling by combining stem cell or patient-derived primary cell-based models for cartilage and synovium ( Fomby et al, 2010 ; Smeriglio et al, 2015 ; Tian et al, 2016 ; Li et al, 2017 ; Lin et al, 2019 ) as well as adipose ( Loskill et al, 2017 ) and bone-like tissues ( Mansoorifar et al, 2021 ; Nasello et al, 2021 ). In this context, microfluidic technologies can create an even more dynamic yet more controllable musculoskeletal disease microenvironment.…”
Section: In Vitro Technologies To Model the Cellular And Mic...mentioning
confidence: 99%
“…Moreover, the authors used their miniaturized drug screening tool to recover cartilage-specific OA-like inflammation responses with a treatment. Notably, to further investigate and approximate in vivo- like tissue conditions, increase of microfluidic construct diameter and volumes by twofold increased collagen and glycosaminoglycan biosynthesis as well as the corresponding dynamic construct modulus ( Tian et al, 2016 ). Both studies demonstrate well that the geometry and macroscopic dimensions of a construct influence the models’ diffusivity as well as topographical molecule gradients that in turn are vital to control parameters for organoid maturation and native tissue-like physiology.…”
Section: In Vitro Technologies To Model the Cellular And Mic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeably, the results of this study demonstrated that the developed model allows replicating the 3D expansion step occurring during the early stages of limb development, overcoming one of the main limitations of other 3D models, such as macropellets, which experience a reduction in cell number over time due to the formation of a necrotic core [ 54 ]. The use of SDGs has been also implemented in microfluidic platforms designed and exploited to select the most suitable concentration and/or combination of growth factors to favor articular chondrocyte proliferation, either in monolayer culture [ 55 ] or hydrogel-based culture [ 56 ]. The low number of cells that can be obtained from patients' biopsies is one of the main limiting factors in ACI procedures, and hence, the optimization of the protocol for chondrocyte expansion represents a crucial step to improve the outcome of this clinical approach.…”
Section: Microfluidics and Bioprinting To Trigger The Translation mentioning
confidence: 99%